Progress and Challenges of grain drying technologies in Indonesia - Engkos Achmad Kosasih; Muhammad Burhanuddin Fauzi; Tresna Priyana Soemardi (BKS-TM Indonesia, 2025)
Grain drying is a vital postharvest stage in Indonesia to maintain quality, reduce losses, and support food security. High moisture levels in rice, maize, coffee, and soybean increase risks of physical damage, nutrient loss, and mycotoxin contamination, lowering market value and competitiveness. Traditional sun-drying is still common among smallholder farmers due to its simplicity and low cost, but it is weather-dependent, unhygienic, and inefficient. To address these issues, mechanical dryers such as flat-bed, fluidized-bed, rotary, and solar-assisted types have been introduced, improving efficiency and moisture uniformity, yet adoption is constrained by high costs, energy requirements, and limited rural infrastructure. Recent advances include microwave drying and Internet of Things (IoT)-based systems that enable real-time monitoring and promote sustainable energy use. However, challenges remain in affordability, renewable energy access, and farmers’ technological literacy. Future research should focus on developing low-cost hybrid dryers powered by renewable sources, integrating digital technologies for precision control, and exploring strategies to preserve nutritional quality and reduce mycotoxins. Strengthening regional collaboration is also crucial to accelerate the adoption of sustainable drying technologies in Southeast Asia. Overall, advancing grain drying technologies offers significant potential to improve energy efficiency, ensure product quality, and reinforce Indonesia’s food security in tropical conditions.